1998
DOI: 10.1007/s001250051034
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a circadian rhythm of insulin release from perifused rat pancreatic islets

Abstract: While there is strong evidence that circadian rhythms are generated in the mammalian suprachiasmatic nucleus (SCN) [1,2] and in the avian pineal gland [3,4], determinations of circadian rhythms in other isolated organs or cells are rare. Only few in vitro investigations of insect tissues or mammalian cells or organs such as intestine, adrenals [5±7], heart cell networks and liver cells [8,9] have shown the existence of circadian rhythms in culture [10,11]. In addition it has been shown that cultured mammalian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
130
0
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(148 citation statements)
references
References 35 publications
14
130
0
4
Order By: Relevance
“…The existence of MT2 receptor on the pancreatic β-cell is accomplished by application of melatonin as isolated islets of rats has phase-shifting effects on the insulin rhythm (34). Moreover, molecular and immunocytochemical studies confirmed the presence of the melatonin receptors MT1 and MT2 in the islets of Langerhans and also in human pancreatic tissue (35).…”
Section: Melatonin Receptors and Its Classificationmentioning
confidence: 83%
See 1 more Smart Citation
“…The existence of MT2 receptor on the pancreatic β-cell is accomplished by application of melatonin as isolated islets of rats has phase-shifting effects on the insulin rhythm (34). Moreover, molecular and immunocytochemical studies confirmed the presence of the melatonin receptors MT1 and MT2 in the islets of Langerhans and also in human pancreatic tissue (35).…”
Section: Melatonin Receptors and Its Classificationmentioning
confidence: 83%
“…Since the intake of food induces insulin secretion, the amount of insulin in plasma follow the daily rhythm in feeding and may exhibit a daily rhythm as well. In contrast, mouse and human pancreatic islet cells have been found to possess circadian activity as well (34,67,68). This concept gives emphasis to the presence of a circadian regulation over pancreatic function.…”
Section: Melatonin and Insulin Secretionmentioning
confidence: 99%
“…The system is hierarchical, the suprachiasmatic nucleus in the hypothalamus being the 'master clock', with additional clock activities in numerous peripheral tissues. In fact, there is some evidence for a circadian rhythm in pancreatic islets [5]. The peripheral clocks are all thought to signal back to the 'master clock' in the suprachiasmatic nucleus.…”
Section: Control Of Circadian Rhythmmentioning
confidence: 99%
“…That insulin secretion is controlled by circadian mechanisms is supported by studies of humans with circadian misalignment, who are reported to show profound perturbations of plasma glucose and insulin levels [8]. The concept is supported by the assumption that there is a circadian clock in pancreatic islets [5]. While it is clear that insulin secretion exhibits a circadian rhythm, it is unclear whether secretion increases or decreases during the night [41,42].…”
Section: Melatonin and Glucose Homeostasismentioning
confidence: 99%
“…En revanche, les taux plasmatiques de MLT sont élevés pendant la nuit et bas pendant la journée. Une étude sur des îlots de Langerhans du pancréas de rat a montré qu'un traitement par la MLT avance la phase de la sécrétion de l'insuline d'environ 9 h, ce qui suggère que la MLT peut influencer directement l'horloge du pancréas [17]. Des études récentes chez la souris ont montré qu'une perturbation des rythmes circadiens est responsable de la survenue de maladies métaboliques, dont le DT2 [18].…”
Section: Variants Rares Du Gène Mtnr1b -éTablissement D'un Lien Fonctunclassified